Analisis Faktor Financial Knowledge, Financial Behavior, Overconfidence, dan Pendapatan terhadap Keputusan Investasi - Yulistiyani, Andriati; Rapini, Titi; Setiawan, Fery (Jurnal Ilmu Manajemen, 2023)
The development of globalization has led the younger generation to enter the world of investment. The rapid development of the increasing number of young investors is due to the role of the Indonesian Stock Exchange (IDX) in socializing investment programs. The program collaborates with the academic community at tertiary institutions by establishing an Investment Gallery which aims to invite the younger generation to increase their interest in investing. This study aims to examine the effect of financial knowledge, financial behavior, overconfidence, and income on investment decisions at the Muhammadiyah University Ponorogo Investment Gallery. The population in this study were investors from the Muhammadiyah Ponorogo University Investment Gallery with as many as 95 respondents. The research method and data analysis used is multiple regression analysis. The results of this study indicate that financial knowledge has an effect on investment decisions, financial behavior has an effect on investment decisions, overconfidence has an effect on investment decisions, while income has no effect on investment decisions.